Karol Libelt’s idea of Slavic philosophy - Brzozowski, Tomasz Tadeusz (Folia Philosophica, 2009)
The paper discusses Karol Libelt’s critique of Hegel’s thought from the perspective of his own standpoint in which he tries to sustain the idea of the immorality of soul and personality of the spirit. In the latter part presuppositions of the idea of Slavic philosophy are presented. Most systematically Libelt has presented his ideas in Samowładztwo rozumu i objawy filozofii słowiańskiej, hence the paper is mostly based on this book. Libelt’s conception was rooted in the critiques of theoretical philosophies, which he finds to be concerned primarily with “the autocracy of reason”. And his critique was directed towards the speculative character of this kind of philosophy. By putting forward the postulate of creation of a new philosophy rooted in act, practicality and activity of agent, Libelt appears as a Slavophil. And he proposes slavophilism as an alternative for speculative character of Hegelian philosophy and its panlogism. The essence of Slavic philosophy, according to Libelt, is the act in which the entirety of the spirit, originated in the act of the will of knowledge and thought, is being revealed.